Phenology, Distribution, and Diversity of Dung Beetles (Coleoptera: Scarabaeidae) in North Florida's Pastures and Forests. Issue 4 (12th June 2019) - Conover, Derrick; Dubeux, Jose; Martini, Xavier
Abstract: Dung beetles are important to ecosystems as they aid in nutrient recycling and waste removal. In North Florida, there is a high diversity of dung beetles due to the intentional and accidental introduction of non-native species. Understanding patterns and processes on local scales is important for conservational planning. The aim of this study was to evaluate how dung beetle communities respond to different dung sources, forage composition, and habitat types. We surveyed for the presence and distribution of dung beetles in an open field and forest as well as in three types of pasture forage designs. In the first experiment, four transects with pitfall traps from forest to open field were established with either horse, pig, or cow feces bait. In the second experiment, three cattle grazing systems with different forage species were tested with only cow feces. In the first experiment, 16 species were identified between the field and forest sites including native and exotic species. Although the dung type had little effect on beetle distribution, a significantly different distribution of dung beetles between the field and forest was observed. Only one species, Onthophagus hecate Panzer (Coleoptera: Scarabaeidae) showed no preference between open field and forest habitat. During this second experiment, no difference in dung beetle distribution was found between the three types of pasture assemblages. This study supports habitat type as a driver of interspecies distribution and diversity of dung beetles in North Florida.